TECHNICAL EDUCATION FOR SUSTAINABLE DEVELOPMENT: EXPERIMENTAL LEARNING THROUGH PICO-HYDRO PROPELLER TURBINE DESIGN AND IMPLEMENTATION - Rumagit, Paul Maarthen; Pangow, Tammy Tinny; Siwi, Herotje; Tulung, Fransiscus Josep (CV. TOTUS TUUS, 2025)
Indonesia possesses immense hydropower potential, yet much remains untapped, especially for rural electrification where reliable access to electricity is still limited. Pico-hydro technology, utilizing small-scale water turbines, represents a promising, environmentally friendly solution for decentralized power generation in remote areas. However, the effectiveness of conventional pico-hydro turbines is often constrained by low or variable water flow, necessitating innovation in turbine design. This research aimed to design, fabricate, and experimentally evaluate a small-scale vertical-blade propeller (pico-hydro) turbine, with a particular focus on the effects of blade number and inclination angle on turbine performance. An experimental method was conducted in a laboratory setting using variations of blade geometry, type, and inclination angle under controlled water flow conditions. The results demonstrated that both water discharge and head height substantially affect turbine output, with the optimal configuration—standard (curved) blades, four in number, at a 30° angle—achieving a maximum power output of 200 Watts and superior efficiency compared to other tested variants. These findings validate that careful optimization of blade geometry can significantly enhance the performance of pico-hydro turbines, contributing valuable empirical data for rural electrification strategies. The study’s practical implication is clear: locally manufactured turbines with optimized blade design can enable more sustainable and widespread rural electrification. Further research is recommended to assess long-term field performance and investigate advanced materials and digital design tools for even greater efficiency and adaptability.